12
$\begingroup$

Given $\lambda$ an integer partition of $n$, let $h_{ij}(\lambda)$ denote the hook length of cell $(i,j)$ in the Young diagram of $\lambda$.

Is there a closed formula or a generating function for the following sequence? $$f_n=\sum_{\lambda\vdash n}\sum_{(i,j)\in\lambda}(-1)^{i+j}\cdot h_{ij}(\lambda)$$

$\endgroup$
4
  • $\begingroup$ Why mention $\lambda'$? $\endgroup$ Apr 2 at 21:08
  • $\begingroup$ You need $\lambda'$ to compute hook length. $\endgroup$ Apr 2 at 21:11
  • 1
    $\begingroup$ Depends what you call "compute". I guess you meant writing an algebraic formula for $h_{ij}$ in terms of $\lambda_i$ and $\lambda'_j$. I was thinking of a visual definition of the hook length from the diagram. $\endgroup$ Apr 2 at 21:14
  • 1
    $\begingroup$ I see. I will minimize the confusion by editing those lines in my post which I just noted that Matthieu did already. $\endgroup$ Apr 2 at 21:33
20
$\begingroup$

The hook length $h_{ij}(\lambda)$ counts the number of boxes directly below or directly to the right of box $(i,j)$. (I picture the Young diagram of $\lambda$ as having the corner $(0,0)$ located in the upper left.) With this in mind, the alternating sum $\sum_{(i,j)\in \lambda}(-1)^{i+j}h_{ij}(\lambda)$ can be expanded as a signed sum over all the boxes in $\lambda$. We see that a box $(i,j)$ contributes $+1$ if both $i,j$ are even, $-1$ if both $i,j$ are odd, and $0$ otherwise. Using this description we see that $$\sum_{(i,j)\in \lambda}(-1)^{i+j}h_{ij}(\lambda)=\left\lceil \frac{\lambda_1}{2}\right\rceil-\left\lfloor\frac{\lambda_2}{2}\right\rfloor+\left\lceil \frac{\lambda_3}{2}\right\rceil-\left\lfloor\frac{\lambda_4}{2}\right\rfloor+\cdots$$ where $\lambda=(\lambda_1, \lambda_2, \dots)$.

Now we can use a wonderful formula due to Boulet (Theorem 1 in "A Four-parameter Partition Identity") which tells us (after the appropriate specialization) $$\sum_{\lambda}x^{\sum_{(i,j)\in \lambda}(-1)^{i+j}h_{ij}(\lambda)}q^{|\lambda|}=\prod_{k\geq 1}\frac{(1+xq^{4k-1})(1+xq^{4k-3})}{(1-q^{4k})(1-xq^{4k-2})^2}$$ I will call this two variable generating function $H(x,q)$. The generating function $F(q)=\sum_{n\geq 0}f_nq^n$ is given by $$F(q)=\left[\frac{\partial}{\partial x} H(x,q)\right]_{x=1}$$ therefore we start by computing $$\frac{\partial}{\partial x} H(x,q)=H(x,q)\sum_{k\geq 1}\left(\frac{q^{4k-1}}{1+xq^{4k-1}}+\frac{2q^{4k-2}}{1-xq^{4k-2}}+\frac{q^{4k-3}}{1+xq^{4k-3}}\right)$$ and finally setting $x=1$ gives $$F(q)=\left(\prod_{k\geq 1}\frac{1}{1-q^k}\right)\cdot\left(\sum_{n\geq 1}A_nq^n\right)$$ where $\sum_{n\geq 1}A_{n}q^n=\sum_k\left(\frac{q^{4k-1}}{1+q^{4k-1}}+\frac{2q^{4k-2}}{1-q^{4k-2}}+\frac{q^{4k-3}}{1+q^{4k-3}}\right)$. If we expand this last sum, the terms simplify a little bit to give $\sum_{n\geq 1}A_n q^n=\sum_{k\geq 1}\frac{q^{2k-1}}{1-q^{2k-1}}$.

$\endgroup$
0
3
$\begingroup$

This is a follow up note on Gjergji Zaimi's fine response.

It seems that $$\sum_nA_nq^n=\sum_k\frac{q^{2k-1}}{1-q^{2k-1}}=\sum_n\frac{d(n)}{\nu_2(2n)}q^n,$$ where $d(n)$ is the sum of (positive) divisors of $n$ and $\nu_2(m)$ is the $2$-adic valuation of $m$.

Therefore, we obtain the convolution sum $$f_n=\sum_{k=1}^n\frac{d(k)\cdot p(n-k)}{\nu_2(2k)}$$ where $p(m)$ is the number of integer partition of $m$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.